EQUATIONS OF STATE IN EXPLORATION - Meulbroek P. (My University, 2002)
Calculations using equations of state to predict the phase behavior and composition of hydrocarbon species are finding use as an exploration technique. Equations of state give insight into the chemical changes induced in a hydrocarbon mixture by changes in pressure and temperature. Equation of state calculations can be used to estimate the effects of alteration during migration, reservoir filling, and production. Production effects explored include reservoir depressurization and pumping-induced fractionation. Other reservoir management techniques discussed include volume prediction, fluid fingerprinting, and oil quality estimations. Migration effects addressed include gas washing and evaporative fractionation.